THE EFFECT OF VIDEO-BASED GROUP DISCUSSION ON LISTENING COMPREHENSION OF EIGHTH GRADE STUDENTS AT SMP NEGERI 2 SAWAN IN ACADEMIC YEAR 2015/2016 - ., Putu Mas Istri Yanti; ., Prof. Dr. Anak Agung Istri Ngr. Marha; ., Made Hery Santoso, S.Pd, M.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian ini bertujuan untuk menyelidiki apakah ada pengaruh yang signifikan dari Video- Group Discussion pada kemempuan pemahaman mendengarkan siswa kelas delapan. Posttest- Only Control Group digunakan sebagai desain penelitian penelitian ini. Populasi dari penelitian ini adalah 370 siswa kelas VIII SMP Negeri 2 Sawan tahun akademik 2015/2016. Sampel dari penelitian ini adalah 60 siswa yang dipilih dengan menggunakan teknik sampel random atau acak, Hasil analisis menunjukkan bahwa ada pengaruh yang signifikan dari Video –based Group Discussion tentang pemahaman mendengarkan siswa kelas delapan (tobs = -6,712, sig. 0.000). Siswa yang diajarkan menggunakan Video-based Group Discussion lebih baik dalam pemahaman mendengarkan.Kata Kunci : Pemahaman mendengarkan, Video-based Group Discussion This study aimed to investigate whether there was a significance effect of Video- based Group Discussion on listening comprehension of eighth grade students. Post-test Only Control Group was used as research design of this research. The population of this study was 370 the eighth grade students of SMP Negeri 2 Sawan academic year 2015/2016. The sample of this study was 60 students selected by random sampling. The result of analysis showed that there is significant effect of Video-based Group Discussion on listening comprehension of eighth grade students (tobs=-6.712, significance 0.000). The students who were taught using Video-based Group Discussion achieved better in listening comprehension.keyword : Listening comprehension, Video based Group Discussion.